2014
DOI: 10.1021/es5016907
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers, 2,2′,4,4′,5,5′-Hexachlorobiphenyl (PCB-153), and p,p′-Dichlorodiphenyldichloroethylene (p,p′-DDE) Concentrations in Sera Collected in 2009 from Texas Children

Abstract: Polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs) and p,p′-dichlorodiphenyldichloroethylene (p,p′-DDE) have been measured in surplus serum collected in 2009 from a convenience sample of 300 Texas children (boys and girls) in the birth to 13 years of age range. Serum concentrations of traditional persistent organic pollutants such as 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB-153) and p,p′-DDE did not change consistently with age. By contrast, serum concentrations of tetra-, penta-, and hexa-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 20 publications
7
29
3
Order By: Relevance
“…Although these compounds are ubiquitous in the environment, certain populations are disproportionately exposed. Studies have consistently shown that children have the highest serum levels of PBDEs compared with other age groups (Lunder et al, 2010), peaking between 2-6 years (Sjodin et al, 2014b). This is thought to be due primarily to increased dust ingestion in the first years of life, because of time spent on the floor and frequent hand-to-mouth behavior (Jones-Otazo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although these compounds are ubiquitous in the environment, certain populations are disproportionately exposed. Studies have consistently shown that children have the highest serum levels of PBDEs compared with other age groups (Lunder et al, 2010), peaking between 2-6 years (Sjodin et al, 2014b). This is thought to be due primarily to increased dust ingestion in the first years of life, because of time spent on the floor and frequent hand-to-mouth behavior (Jones-Otazo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…11 More recently, among 300 Texas children 0-13 years, serum concentrations were highest in the 4-6 year age group prompting the authors to call for additional studies to characterize young children's exposure to PBDEs and to identify factors that contribute to these high exposures. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Children have higher levels of PBDEs in their bodies than adults, with the highest body burdens being reported for children of approximately 3 years of age. 4,5 …”
Section: Introductionmentioning
confidence: 99%